Meningkatkan Estimasi Reliabilitas Instrumen Pilihan Ganda dengan Memperhatikan Probabilitas Guessing - Diah Oga Nusantari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
Reliability coeficient is a number which refer to stability result of an instrument measurement. The higher coeficient of reliability, the hingher trusted result of the instrumen will be. The degree of confidence of an intsrument, is expressed by reliability coefisient. For multiple choice instrument, estimation of reliability mostly calculated by KR-20. KR 20 formula calculate estimation of reliability instrumen by using correct score method. This study aims to comphere estimation of reliability coefficient by using KR-20 formula and by considering guessing probability. Hopely by considering guessing factor, estimation of reliability coefficient will increased Key words: Instrument, Multiple choice, Reliability, Guessing probability